Fretting Fatigue: Advances in Basic Understanding and Applications 2003
DOI: 10.1520/stp10766s
|View full text |Cite
|
Sign up to set email alerts
|

Fretting Fatigue Behavior of Titanium Alloys

Abstract: A discussion of experimental studies to characterize the fretting fatigue behavior of titanium alloys is presented. This includes studies to evaluate the effects of normal pressure, contact material conditions, surface treatments, and environment. In addition, concepts of normal pressure threshold and damage threshold as related to fretting fatigue of titanium alloys are discussed. Finally, this paper is concluded with suggestions for future research efforts that are essential to improve understanding of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A statistic reveals that 1/6 of aircraft engine incidents resulting from high-cycle fatigue are attributed to fretting fatigue. 40 In response to this issue, Shi et al 38,41 created a device, as shown in Fig. 1(c).…”
Section: Development Of In Situ Sem Fatigue Testing Technologymentioning
confidence: 99%
“…A statistic reveals that 1/6 of aircraft engine incidents resulting from high-cycle fatigue are attributed to fretting fatigue. 40 In response to this issue, Shi et al 38,41 created a device, as shown in Fig. 1(c).…”
Section: Development Of In Situ Sem Fatigue Testing Technologymentioning
confidence: 99%
“…31,32 However, there are very few quantitative models that account for the development and growth of defects from smooth surfaces. Those models cited in the literature, [33][34][35][36] critically are dependent upon the application of Linear Elastic Fracture Mechanics (LEFM). This application of LEFM parameters to the modelling of microstructural dependent crack grow is considered to be inappropriate and a comment on this effect is given later.…”
Section: Modellingmentioning
confidence: 99%